Herbert Simon’s Epistemological Itinerary on the Limits of Rationality - Paço Cunha, Elcemir (Organizações & Sociedade, 2022)
This article investigates Herbert A. Simon’s epistemological itinerary with regard to the limits of rationality presented in his book Administrative Behavior, published in 1947. The investigation, grounded in materialism, explores his epistemological itinerary based on two categories of analysis: the key sources used to establish the limits of rationality and the way in which the author proceeded to investigate this object. The investigation revealed that the development of the limits of rationality gained ground in the early decades of the twentieth century and that numerous texts, which reflected a particular trend at the time, served as a conduit for Simon. Simon’s assimilation of this development took place within the boundaries of empiricism, continuing the critique of the unrealism of the maximizing agent in the neoclassical school. In procedural terms of research on the limits of rationality, Simon made specific observations and, based upon them, logical inferences regarding the consequences of the limits of rationality for certain organizational aspects.